ANALISIS PENDAPATAN RETRIBUSI PASAR DI KABUPATEN BANYUMAS MENGGUNAKAN UJI ANOVA SATU ARAH - Prabowo, Agung; Susilawati , Susi; Paramita Amitarwati , Diah (Universitas Perwira Purbalingga, 2021)
One of the local retribution is the market retribution. This market retribution is included in the general service levy which has a potential contribution to the improvement of development and community welfare. To determine the market levy rate, the government uses the Market Levy Collection Implementation Guideline which categorizes the market into class I, II, III and IV markets. In managing market retribution, the Banyumas Regency Government gives authority to the Department of Industry and Trade. In practice, market management is divided into several service technical management units (STMU), namely (1) STMU Market for East Banyumas Region, (2) STMU Market for West Banyumas Region, (3) STMU Market for Purwokerto I Region, and (4) STMU Pasar Purwokerto II Region. Each STMU has its own working area which consists of a combination of several market classes. The purpose of this study was to analyze the market retribution income based on the STMU of the market area in Banyumas Regency. This study uses secondary data in the form of market retribution income data in January-July 2021 obtained from the Banyumas Regency Industry and Trade Office. Based on the results of the analysis with the one-way ANOVA test, it was found that there were differences in market retribution income for the four markets STMU in Banyumas Regency. The average retribution income for the STMU Pasar areas of East Banyumas, West Banyumas, Purwokerto I and Purwokerto II is IDR 119,860,439, IDR 128,914,779, IDR 77,952,250, and IDR 49,736,959.